Koniok gorbunok, ili, Tsar-devitsa = Le petit cheval bossu, ou, La Tsar-demoiselle = The little humpbacked horse, or, The Tsar-maiden : a magical ballet in 4 acts and 7 scenes /: Le petit cheval bossu, ou, La Tsar-demoiselle = The little humpbacked horse, or, The Tsar-maiden : a magical ballet in 4 acts and 7 scenes. (2012) - Unknown
No abstract available